Energy Analytics for Development : Big Data for Energy Access, Energy Efficiency, and Renewable Energy - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
With unprecedented speed and scale, digital transformation is affecting multiple industries, including energy. A combination of technologies, and a more complex world demanding greater agility and new competences impact all aspects of the energy sector and manifest themselves in changing patterns of consumption, new ways of asset optimization, and cross-industry partnerships. 'Smart solutions' are a product of this transformation and energy data are its source. By nature, the energy sector generates vast amounts of big data through meters, sensor networks, customer payments, credit history, satellite imagery, etc. It is not surprising that private and public energy companies are turning to the idea of leveraging big data analytics for performance optimization and improved service delivery. The transition to a digitized energy sector will not happen on its own, and a number of enablers are required to facilitate this change. Beyond improved digital infrastructure, digital skills and analytics capabilities will need to be strengthened. This new solutions brief aims to encourage the use of big data analytics in the energy sector by outlining opportunities and identify cases for where the use of big data analytics could help better address challenges faced by the energy sector today.